PENGARUH INDEPENDENSI AUDITOR DAN BESARAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK - Tjan, Juliyanty Sidik (Patria Artha Journal of Accounting dan Financial Reporting, 2018)
This study aims to examine the effect of audit independence and fees on audit quality on KAPauditors in Makassar City. Data analysis method used is SEM analysis with PLS program. Theresults of this study indicate that the independence variables and audit fees have a positive effect on audit quality.